2017
DOI: 10.18632/oncotarget.23813
|View full text |Cite
|
Sign up to set email alerts
|

MRI texture analysis in predicting treatment response to neoadjuvant chemoradiotherapy in rectal cancer

Abstract: To evaluate the importance of MRI texture analysis in prediction and early assessment of treatment response before and early neoadjuvant chemoradiotherapy (nCRT) in patients with locally advanced rectal cancer (LARC). This retrospective study comprised of 59 patients. The tumoral texture parameters were compared between pre- and early nCRT. Area Under receiver operating characteristic (ROC) Curves [AUCs] were used to compare the diagnostic performance of statistically significant difference parameters and logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 26 publications
0
37
0
Order By: Relevance
“…For the specific problem of associating CRT response via pretreatment T 2 w MRI, a majority of these studies were limited to single‐site, single‐scanner cohorts 32 . While these studies used different texture feature sets, their performance in classifying patients who later achieved pCR using T 2 w MRI is comparable to our own (AUCs ranging from 0.71–0.80), 33–35 but these studies did not report on how their model generalized to data from other sites. Notably, some of these studies 37,38 reported that multiparametric radiomic features could offer enhanced response classification performance for rectal cancers.…”
Section: Discussionmentioning
confidence: 89%
“…For the specific problem of associating CRT response via pretreatment T 2 w MRI, a majority of these studies were limited to single‐site, single‐scanner cohorts 32 . While these studies used different texture feature sets, their performance in classifying patients who later achieved pCR using T 2 w MRI is comparable to our own (AUCs ranging from 0.71–0.80), 33–35 but these studies did not report on how their model generalized to data from other sites. Notably, some of these studies 37,38 reported that multiparametric radiomic features could offer enhanced response classification performance for rectal cancers.…”
Section: Discussionmentioning
confidence: 89%
“…Besides its recent multifold use in oncological imaging in terms of tissue entity discrimination, characterization, and treatment response monitoring, texture analysis also was described as a reproducible tool to quantitatively assess paraspinal fatty infiltration in MRI [ 33 36 ]. In these and other studies, texture heterogeneity was described to be associated with therapy response and clinical outcome [ 35 ]. Besides MRI, the use of texture analysis was investigated on using mammography and in CT in the past to analyze its capability to contribute to computer-aided cancer diagnosis or bone quality measurements [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 98%
“…“Entropy” accounts for a measure of randomness in pixel distribution and may depict clinically relevant changes in vertebral micro-architectural alterations. Other groups also investigated on the reliability of different texture parameters and proved that features like kurtosis, skewness, and uniformity showed good results in diagnostic and monitoring quality in cancer imaging [ 34 , 35 ]. The described arbitrarily detected texture features are inherently dependent on imaging properties like resolution, noise, and scan parameters (repetition time, echo time, and receiver bandwidth) [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nie et al using artificial neural network as classifier found that radiomic features extracted from T1/ T2W, diffusion-weighted (DW) and dynamic contrastenhanced (DCE) MR images could enhance the predictive power of pathologic response after preoperative nCRT for LARC [34]. In another study, Meng et al used MRI texture analysis for nCRT response prediction and found several textures such as standard deviation (SD), kurtosis, and energy; and uniformity were statistically different between responder and non-responder groups [35]. Horvat N et al used MR images to compare value of T2W radiomic textures compared with qualitative assessment at T2W and DW imaging for diagnosis of clinical complete response in patients with LARC after nCRT.…”
Section: Discussionmentioning
confidence: 99%